Budget Participation on Managerial Performance With Budgetary Justice As A Mediation Variable - Kirana, Ardilla Ayu; Kusuma, Emeralda Ayu (IJIBE (International Journal of Islamic Business Ethics), 2024)
The purpose of this study is to obtain empirical evidence of the influence of budget participation on managerial performance and to obtain empirical evidence of the influence of budget justice as a mediating variable on budget participation on managerial performance. This research is descriptive quantitative research with associative research methods and explanatory research. The data were obtained using primary data in the form of a questionnaire with a sample size of 141 companies in the PT. Surabaya Industrial Estate Rungkut. The data analysis in this study used Structural Equation Modeling (SEM) with the Partial Least Square approach using the WarpPLS application. The results showed that budget participation has a significant direct effect on managerial performance, both before and after including the mediating variables of procedural, distributive, and interactional justice. Procedural, distributive, and interactional justice were found to mediate this relationship. The findings highlight the importance of budget participation and justice in enhancing managerial performance. Procedural, distributive, and interactional justice mediate this relationship, emphasizing that fairness in processes, resource allocation, and interpersonal treatment positively impact performance. This supports fairness, transparency, and respect in decision-making, fostering trust, motivation, and long-term organizational success through ethical leadership and justice-driven practices